Control of Magnetic Properties of Barium Ferrite Thin Films With Unusual Valence Fe - Sakuda, Masahiro; Yamahara, Hiroyasu; Tabata, Hitoshi; Seki, Munetoshi (Frontiers in Materials, 2021)
Thin films of BaFe1-xMxO3 (M = Hf, Zr, and Ce; 0.0 ≤ x ≤ 0.75) were fabricated using pulsed laser deposition and their magnetic properties were investigated. X-ray diffraction analysis indicated that oxygen-deficient BaFeO2.5 with a monoclinic structure was formed when the deposition was conducted using a non-substituted target (x = 0.0). The as-grown BaFeO2.5 films were converted into fully oxidized BaFeO3 with a perovskite structure by low-temperature oxidation in an ozone atmosphere. In contrast, the as-deposited films of Hf, Zr, and Ce-substituted films exhibited a perovskite structure, and their crystallinity did not change after low-temperature ozone annealing. The magnetic transition temperature Tc of the BaFeO3 film was 110 K, whereas the substituted BaFeO3 films showed ferromagnetic behavior even at 300 K. These results can be attributed to the weakening of the antiferromagnetic super-exchange coupling among Fe ions owing to the lattice expansion in the substituted BaFeO3. In addition, the magnetization of the films was found to increase with the decreasing ionic ratio of Fe4+/Fe3+, suggesting that the inherent carrier-induced ferromagnetic interaction is dominant in the films.